PENGARUH PENDAPATAN ORANG TUA DAN GAYA PERGAULAN TERHADAP PERILAKU KEUANGAN MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Wendi Crisdianto Tamba; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to obtain knowledge about the influence of parental income and social style on financial behavior of students of the economic education study program, HKBP Nommensen Pematang Siantar University This type of research is a quantitative research with a quantitative descriptive data analysis approach with the testing medium used is SPSS 22. The total population in this study was 267 people, and the sample used was 160 people The sample collection technique used was simple random sampling. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and determination coefficient (R2). obtained a = 17.510, b1 = 0.494, b2 = 0.272 and e = 3.371. Contribution can be determined by squaring the simple influence "R" which can be formulated as follows: 100. r2 % Contribution between parents' income to students' financial behaviour Data r = 0.593, then r2 = 0.3516. Thus, the influence of parents' income on students' financial behavior is expressed in the form of percentages as follows: 100. r2 % = 35.16%. The contribution between social styles to students' financial behavior was obtained with data r = 0.509, then r2 = 0.2591. Thus, the influence of social style on students' financial behavior is expressed in the form of percentages as follows: 100. r2 % = 25.91%. The contribution between parents' income and social style to students' financial behavior was obtained data r = 0.593, then r2 = 0.3516. Thus, the influence of parents' income and social style on students' financial behavior is expressed in the form of percentages as follows: 100. r2 % = 35.16%.